The role of the right temporoparietal junction in social interaction: how low-level computational processes contribute to meta-cognition - Decety, Jean; Lamm, Claus (The Neuroscientist (Baltimore, Md.), 2007)
Accumulating evidence from cognitive neuroscience indicates that the right inferior parietal cortex, at the junction with the posterior temporal cortex, plays a critical role in various aspects of social cognition such as theory of mind and empathy. With a quantitative meta-analysis of 70 functional neuroimaging studies, the authors demonstrate that this area is also engaged in lower-level (bottom-up) computational processes associated with the sense of agency and reorienting attention to salient stimuli. It is argued that this domain-general computational mechanism is crucial for higher level social cognitive processing.